The interference of body position with vibration transmission during training on a vibrating platform - Roberta Pires Vasconcellos; Gustavo Ricardo Schütz; Saray Giovana dos Santos (Universidade Federal de Santa Catarina, 2014)
Whole-body vibration training on vibrating platforms is widely used for physical exercise, health promotion and physical rehabilitation. The position on the platform is one of the factors responsible for the transmission of vibrations to the body segments of individuals. Therefore, the objective of this study was to compare the characteristics of vibrations transmitted to the body segments of adults between two body positions and different vibration intensities. Twenty intentionally selected subjects (10 men and 10 women), with a mean age of 27.8 } 2.9 years, participated in the study. The data were acquired with a triaxial accelerometer attached to the subject's body using a vibrating platform at frequencies of 20, 35, 50, and 70 Hz and displacement amplitudes of 2.0 and 6.0 mm in the extended and flexed positions. Descriptive and inferential statistics was applied (p ≤ 0.05). Significant differences in the vibration magnitude and transmissibility were observed between body positions at all intensities analyzed, with greater attenuation of vibrations in the flexed position, especially during passage of the vibratory stimulus through the lower limbs. It was concluded that the body position adopted by the subjects on the vibrating platform directly affects the transmission of vibration. The flexed position was found to be the most suitable for the application of this training method by ensuring better body stability on the platform and promoting more effective attenuation of vibrations, thus preventing the occurrence of unintended acceleration in the head.